Legal Protection for Auction Winners Against Objection Lawsuits Regarding Mortgage Rights Objects for which Execution Has Been Requested (Study of Decision Number 72/Pdt.Bth/2019/PN.Kdl) - Ariyani, Sahida; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine and analyze the implementation of auctions and the protection of auction winners against objections related to mortgage objects that have been requested for execution (study of decision Number 72/Pdt.Bth/2019/PN.Kdl). The research method used is normative juridical. Data was obtained through documentation techniques, namely researchers collecting relevant laws and court decisions. Data analysis was carried out by data reduction, data display, and decision making. The purpose of this study was to examine the auction implementation process against objections related to mortgage objects that have been requested for execution. The results of this study are that the auction implementation has been in accordance with the Regulation of the Minister of Finance (PMK) Number 122 of 2023. The auction object that has been sold is the right of the auction winner. If the debtor still controls the auction object, the auction winner can ask the KPKNL to issue a gross minutes to vacate the auction object and ask the District Court for assistance to send a bailiff. In addition, the objections filed by the opponents to the auction winner are repressive legal protection. In decision No. 72/Pdt.Bth/2019/PN.Kdl, the panel of judges rejected the objections from Pelawan I and Pelawan II. Thus, the vacating of the auction object will continue and provide legal protection for the auction winner for the auction object that has been purchased. Thus, in this study legal protection is present to fulfill the interests of the auction winner.